Percepción social frente al riesgo deslizamiento en el sector Charquiyacu perteneciente al cantón Caluma, provincia de Bolívar, Ecuador - Morales Narváez, Leidy Rubí (2022)
The objective of the research was to determine the level of social perception regarding the risk of slippage in the Charquiyacu sector, for this the situational status of the slippage risk was established, to know the social perception and to propose risk reduction measures. The applied methodology had a mixed approach, the type of descriptive research with a cross-sectional design; The universe was 751 people, the sample applied the adjustment 64 families, the observation research techniques, the interview with key informants and the survey. The results were that in the Charquiyacu sector it is very prone to landslides, due to the high slopes, deforestation, high rainfall, when an adverse event occurs, a part of the population manifests insecurity and uncertainties, the population considers that the establishment of walls in housing construction and a risk management education process are risk mitigation measures. Keywords: Slipping, social perception, situational diagnosis, risk prevention. risk management, insecurity, uncertainty.